The power of many – Increasing the performance of wireless ad hoc networks with cooperative communication - Tissari, Jari (fi=Turun yliopisto|en=University of Turku|, 2017)
The world of today is more connected than ever before. With the rapid development of mobile devices and wireless communication technology, producing and globally distributing large amounts of data, such as video and audio files, has been made possible for billions of users around the world. To support the increasing amount of users and data transferred over the air, continuous effort on development of more efficient wireless communication algorithms and technology is required from the scientific community. During the last decade or so, a prevalent impression inside the wireless research community has come to be that the capacity of large wireless networks can be maximized by collaboration between groups of users. By using terminal cooperation, limited network resources such as transmit power and bandwidth can be used more effectively, leading to increased aggregate network capacity and coverage. In wireless networks in which terminals communicate only with nearby nodes, and in which the number of simultaneous transmissions is maximized, the transmitting powers of the terminals and the range of transmissions can be made as small as possible, leading to reduction in the interference that transmissions cause on each other. In this thesis, I study cooperative and distributed communication in the physical layer of wireless communication systems. Together with presenting the basic cooperative communication scenario and transmission schemes, I address a number of relevant design issues, together with practical system design above the physical layer in mobile ad hoc networks. I also discuss the theoretical capacity of cooperative wireless networks and present capacity formulas for networks with different characteristics. As my own novel scientific contribution, I propose a distributed beamforming algorithm for orthogonal frequency division multiplexing -based systems, that can join any number of transmitters in cooperation to form a distributed beamforming antenna array. Based on the results gathered from extensive simulations, I propose optimal parameter values for the algorithm operating in different communication environments. The main claim I make in this thesis is that cooperation between groups of terminals can increase the capacity of wireless communication networks, and the capacity of individual users operating in such networks. Furthermore, the outage and error probabilities can be reduced, compared to noncooperative systems using similar transmission parameters. By optimizing a network for cooperative use, terminal transmission powers can be reduced, also leading to reductions in interference and consumption of energy.